Evidence for the Interior Evolution of Ceres from Geologic Analysis of Fractures. Issue 19 (14th October 2017) - Scully, J. E. C.; Buczkowski, D. L.; Schmedemann, N.; Raymond, C. A.; Castillo‐Rogez, J. C.; King, S. D.; Bland, M. T.; Ermakov, A. I.; O'Brien, D. P.; Marchi, S.; Longobardo, A.; Russell, C. T.; et al.
Abstract: Ceres is the largest asteroid belt object, and the Dawn spacecraft observed Ceres since 2015. Dawn observed two morphologically distinct linear features on Ceres's surface: secondary crater chains and pit chains. Pit chains provide unique insights into Ceres's interior evolution. We interpret pit chains called the Samhain Catenae as the surface expression of subsurface fractures. Using the pit chains' spacings, we estimate that the localized thickness of Ceres's fractured, outer layer is approximately ≥58 km, at least 14 km greater than the global average. We hypothesize that extensional stresses, induced by a region of upwelling material arising from convection/diapirism, formed the Samhain Catenae. We derive characteristics for this upwelling material, which can be used as constraints in future interior modeling studies. For example, its predicted location coincides with Hanami Planum, a high‐elevation region with a negative residual gravity anomaly, which may be surficial evidence for this proposed region of upwelling material. Key Points: We identify all ≥1 km wide linear features outside impact craters: most are secondary crater chains and there is one set of pit chains Pit chains are the surface expression of subsurface fractures, and they reveal that the localized outer layer is thicker than Ceres's average We propose that a region of upwelling material, resulting from convection/diapirism, formed the pit chains, and we derive its characteristics